Communication Strategy of Content Collision Agency in Promoting the Blibli.com Brand - Nofrizal, William Ardo; Delliana, Santi (Research Center and Case Clearing House PPM School of Management, 2021)
The digital age has led to the emergence of many companies such as E-commerce, which in the marketing process, not only do marketing through offline media but also have penetrated online or digital media. BliBli.com promotes its brand in collaboration with the digital agency Content Collision to be able to provide SEO (Search Engine Optimization) that can increase PageRank on Google. The purpose of this research is to find out how the communication strategy is carried out by the Content Collision Agency. The research method used is descriptive qualitative data collection through interviews, observations, and study documents. The results showed that the communication strategy used by the Content Collision Agency in promoting BliBli.com was by managing BliBli's blog to be more interesting. Content contained on the website of articles, Slideshare, infographics, and live reports in the field, given a call to action on each document that has made. The content is SEO friendly, up to date, creative, informative, entertaining, distributed via online media, and accompanied by backlinks such as QR code and action buttons (buy now). This method makes it easier for readers to be able to get products and promotions available on Blibli.com. Readers can also share by clicking the share that serves as an expression to express like the article and want to share the information by others or just provide feedback for the content through comments. Reviews of products or services from the brand can increase the number of views and also to increase sales.